Management of head and neck cancer of unknown primary: A phase IV study by DAHANCA - Nielsen, Signe Bergliot; Lyhne, Nina Munk; Andersen, Maria; Plaschke, Christina Caroline; Gothelf, Anita Birgitte; Johansen, Jørgen; Maare, Christian; Farhadi, Mohammad; Godballe, Christian; Primdahl, Hanne; Holm, Anne Ivalu Sander; Alsner, Jan; et al. (European journal of cancer (1990), 2025)
Diagnostic and therapeutic management of patients with head and neck squamous cell carcinoma of unknown primary (HNSCCUP) remains a challenge. The aim of the present phase IV study was to assess adherence to the current Danish guidelines and evaluate the treatment outcome in HNSCCUP patients. Prospectively collected data in the DAHANCA database from patients treated between 2014 and 2020 was evaluated. The median follow-up was 6.7 years. Treatment included definitive neck dissection (dND), primary (chemo-)radiotherapy ((C-)RT), neck dissection (ND) followed by postoperative (C-)RT (ND + (C-)PORT). Outcome were reported as five-year estimates of loco-regional failure (LRF), ultimate LRF (ULRF), disease specific mortality (DSM), overall survival (OS), and toxicity scores ≥ 3. A total of 288 patients were treated, of which 254 (88 %) received treatment with curative intent and were eligible for adherence assessment. These were allocated to dND (n = 60), (C-)RT (n = 81) and ND + (C-)PORT (n = 113). The HPV/p16 status was known in 94 % of patients with 109 (43 %) positive cases. The 5-year LRF, DSM, and OS for patients treated with curative intent was 22 %, 15 % and 73 %, and in patients with p16 positive disease 16 %, 5 %, and 85 %. The overall guideline adherence was 76 % (192/254). In the adherent group the LRF, ULRF, DSM, and OS were 22 %, 11 %, 16 %, and 73 %, respectively. The study revealed good treatment outcome measures in HNSCCUP patients subject to the Danish guidelines, comparable to other head and neck cancer patients. The observed guideline-deviations did not affect outcome. [Display omitted] •Failure and survival outcome in HNSCCUP were comparable with other HNSCCs.•5-year overall survival in HNSCCUP patients treated with curative intent was 73 %.•p16 is a significant prognostic marker in HNSCCUP.•The 5-year OS was 85 % in p16 positive patients and 63 % in p16-negative patients.•Salvage evened out loco-regional failure rate differences between treatment groups.